2020
DOI: 10.1017/s136672892000022x
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between emotion and modality in the Foreign-Language effect on moral decision making

Abstract: This study examined whether the Foreign-Language effect, an increase in bilinguals’ rate of rational decisions to moral dilemmas in their foreign versus their native language, is influenced by emotion and the modality in which the dilemmas are presented. 154 Dutch–English bilinguals were asked to read and listen to personal and impersonal moral dilemmas in Dutch or in English. Importantly, the reading task had the character of a self-paced reading task to resemble the listening task as closely as possible. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…The occurrence and magnitude of the FLE may also depend on the modality in which problems and dilemmas are presented. As previously mentioned (see the Etiology of the FLE), the presentation modality of moral dilemmas has been shown to influence the occurrence of the FLE in proficient bilinguals (Brouwer, 2019(Brouwer, , 2020. Another factor that appears to be important for the presence of the FLE is the distinction between personal and impersonal dilemmas.…”
Section: Methodological Design Featuresmentioning
confidence: 71%
See 1 more Smart Citation
“…The occurrence and magnitude of the FLE may also depend on the modality in which problems and dilemmas are presented. As previously mentioned (see the Etiology of the FLE), the presentation modality of moral dilemmas has been shown to influence the occurrence of the FLE in proficient bilinguals (Brouwer, 2019(Brouwer, , 2020. Another factor that appears to be important for the presence of the FLE is the distinction between personal and impersonal dilemmas.…”
Section: Methodological Design Featuresmentioning
confidence: 71%
“…The relative emotionality of a native vs a foreign language has been argued to be modulated by factors such as age of acquisition (AoA), language proficiency, language use and immersion, and (emotional) context of learning (Caldwell-Harris, 2015; Degner, Doycheva & Wentura, 2012; Dewaele, 2010; Sheikh & Titone, 2016). Recent findings also suggest that the extent to which the FLE occurs in proficient bilinguals can be influenced by the modality in which moral dilemmas are presented (auditory vs written) (Brouwer, 2019, 2020). Brouwer (2020), for example, reported an effect of foreign language when a sample of Dutch–English bilinguals listened to moral dilemmas in Dutch or English, but failed to report an effect when a different sample of Dutch–English bilinguals read the same dilemmas.…”
Section: Etiology Of the Flementioning
confidence: 99%
“…Finally, because we manipulated accents, the dilemmas were presented in auditory modality. Previous studies that have looked at the effect of modality (written vs. auditory) on the FLe [ 8 , 9 , 10 ]. Muda and collaborators have suggested that modality of observation does not seem to explain the variability observed in the FLe, however, in their study they used a text-to-speech system to generate the audio dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…To test the possibility of a foreign accent effect, we presented participants with the well-attested trolley and footbridge dilemmas [ 6 , 7 ], as in Costa et al’s (2014) study, with two exceptions. We did not manipulate the language of presentation but the accent, native versus foreign, and we presented the dilemmas not in written but in auditory form [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, even the issue of whether FLe exists at all remains unresolved: some studies using FL populations have shown that foreign language decreases cognitive biases and increases benefit-maximizing inclinations (Keysar et al 2012;Costa et al 2014a;Geipel et al 2016;Dylman and Champoux-Larsson 2020), while others show the opposite (Hayakawa et al 2017;Muda et al 2018;Mills and Nicoladis 2020); some studies using highly proficient, acculturated bilinguals have found FLe (Brouwer 2020;Miozzo et al 2020), while others have not (Čavar and Tytus 2018; Brouwer 2019; Dylman and Champoux-Larsson 2020).…”
Section: Hypothesis Predictions For Heritage Speakersmentioning
confidence: 99%